Exploring the Co-creation Value of Residents to Tourists From the Perspective of Place Attachment and Economic Benefits - Niu, Han-Jen; Chen, Mei-Jen (Frontiers in Psychology, 2022)
Local development enhances the economic capacity and quality of life of the residents and, in particular, attracts tourism to the area. The co-creative value of the residents and the tourists can improve the consensus of the residents on the sustainable development of the place. This study focuses on the factors influencing the co-creation of value between residents and visitors in the Tamsui area near Taipei. The research hypothesis is based on the components of local attachment, economic benefits brought by tourists, environmental costs, social and cultural welfare of the place, life satisfaction of the residents, and the value of co-creation between residents and tourists. A total of 430 questionnaires were collected through a questionnaire survey and statistical data were analyzed using a structural equation model, including descriptive statistical analysis, measurement reliability and validity verification, model fit, and structural model analysis to validate the research hypotheses. The study found that place attachment positively and significantly affects the economic benefits, environmental costs, and socio-cultural welfare of residents about tourists. Resident satisfaction is positively and significantly affected by the environmental costs from visitors and by socio-cultural welfare, but there is no significant impact from economic benefits. Finally, based on the findings of the study, practical recommendations were made for enhancing co-creation value between Tamsui residents and visitors.